Effect of Packaging Materials of Aloe VeraLime Juice Container on Physicochemical Properties during Storage - Moktar, Iffah Nadhirah; Mat Ali, Zalilah Murni (Enhanced Knowledge in Sciences and Technology, 2022)
Aloe vera-lime juice (ALJ) is processed drink product which is provide nutrients for consumer but nowadays fruit juice tend to become easily spoiled after storage which is influenced by processing, temperature, packaging materials or storage time. This study investigated the factors involved in ALJ storage to observe its storage duration for the purpose of nutrient preservation and quality. Therefore, the ALJ was produced and pasteurized at 95℃ for 1 min. Different packaging materials namely PET bottle, brown glass bottle and colorless glass bottle in 250ml batches and stored for 6 weeks at room (28℃) and refrigeration (4℃) temperature. During the study, brown glass bottle showed significantly higher in pH value than other packaging materials at 28℃ and 4℃ which is 2.83 and 3.21, respectively. Following with the titratable acidity (TA) which is inversely proportional with pH, brown glass bottle demonstrated the lowest TA value. While for total soluble solid (TSS), ALJ stored in PET bottle showed the increased of sucrose from 6.77°Brix to 7.23°Brix for both temperature after 6 weeks. After 6 weeks, ALJ in PET bottle become darker, greener and yellower in colour compared others. While, brown glass bottle has significantly higher value of total phenolic content (TPC) with 0.234 mg GAE/g at 28℃ and 0.238 mg GAE/g at 4℃ after 6 weeks storage. Sensory evaluation showed that the most acceptance of ALJ among panelist were stored in brown glass bottle. According to the study, brown glass bottle has resulted as the best packaging material to preserved nutrient and quality of ALJ.